Fish-derived low molecular weight components modify bronchial epithelial barrier properties and release of pro-inflammatory cytokines. (August 2019) - Kalic, Tanja; Ellinger, Isabella; Kamath, Sandip D.; Palladino, Chiara; Mayr, Vanessa; Tscheppe, Angelika; Ruethers, Thimo; Waltl, Eva E.; Niederberger, Verena; Lengger, Nina; Radauer, Christian; Hafner, Christine; et al.
Highlights: Fish parvalbumins are internalized by bronchial epithelial cells and transported across the epithelial monolayers. Parvalbumins do not affect the epithelial barrier properties. Low molecular weight components from fish meat modify physical and immunological properties of the epithelial barrier. Low molecular weight components from bony versus cartilaginous fish display different effects on epithelial cells. Different effects on epithelium may play a role in differential sensitizing capacities of the two fish classes. Abstract: The prevalence of fish allergy among fish-processing workers is higher than in the general population, possibly due to sensitization via inhalation and higher exposure. However, the response of the bronchial epithelium to fish allergens has never been explored. Parvalbumins (PVs) from bony fish are major sensitizers in fish allergy, while cartilaginous fish and their PVs are considered less allergenic. Increasing evidence demonstrates that components other than proteins from the allergen source, such as low molecular weight components smaller than 3 kDa (LMC) from pollen, may act as adjuvants during allergic sensitization. We investigated the response of bronchial epithelial cells to PVs and to LMC from Atlantic cod, a bony fish, and gummy shark, a cartilaginous fish. Polarized monolayers of the bronchial epithelial cell line 16HBE14o- were stimulated apically with fish PVs and/-or the corresponding fish LMC. Barrier integrity, transport of PVs across the monolayers and release of mediators were monitored. Intact PVs from both the bony and the cartilaginous fish were rapidly internalized by the cells and transported to the basolateral side of the monolayers. The PVs did not disrupt the epithelial barrier integrity nor did they modify the release of proinflammatory cytokines. In contrast, LMC from both fish species modified the physical and immunological properties of the epithelial barrier and the responses differed between bony and cartilaginous fish. While the barrier integrity was lowered by cod LMC 24 h after cell stimulation, it was increased by up to 2.3-fold by shark LMC. Furthermore, LMC from both fish species increased basolateral and apical release of IL-6 and IL-8, while CCL2 release was increased by cod but not by shark LMC. In summary, our study demonstrated the rapid transport of PVs across the epithelium which may result in their availability to antigen presenting cells required for allergic sensitization. Moreover, different cell responses to LMC derived from bony versus cartilaginous fish were observed, which may play a role in different allergenic potentials of these two fish classes.